Rattus rattus ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
660. Roof Rat Rattus rattus French: Rat noir / German: Hausratte / Spanish: Rata negra Other common names: Black Rat, Common House Rat, House Rat, Ship Rat Taxonomy. Mus rattus Linnaeus, 1758, “Europe.” Taxonomy of R. rattus and its relatives is currently influx, and the clade might represent 4-6 species in the R. rattus species complex. As currently recognized, six main lineages in the R. rattus clade are recognized as four distinct species: R. rattus (Lineage I, 2n = 38), R. tanezumi (Lineage II, III, and IV, 2n =42 and 2n = 40 in Sri Lankan Lineage IV), R. sakeratensis (Lineage V), and R. tiomanicus (Lineage VI). As currently understood genetically, Lineage I is sister to Lineage II, both of which are sister to Lineage III. The clade containing Lineages I-III aresister to a clade including Lineage IV-VI, Lineage IV and Lineage V being sister to one another with Lineage VI as sister to them both. This phylogeny leaves R. tanezumi paraphyletic. Lineage I and II seem to be the two that spread around the ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Muridae, pp. 536-884 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on pages 830-831, DOI: 10.5281/zenodo.6887260 ...